Periodontal Manifestations in Vertical Root Fractured Teeth - Shenoy, Nina; Shenoy, Arvind (Journal of Health and Allied Sciences NU, 2022)
Vertical root fractures are more commonly encountered following endodontic treatment and in teeth without endodontic treatment, with habits like bruxism and eating coarse, hard food. The teeth most predisposed to fracture are the premolars of the maxilla and mandible, the mesial roots and mesiobuccal roots of the mandibular molars, maxillary molars and the mandibular incisors. Timely identification of cracked teeth and fractures is the key since it permits a conservative and preventive approach. Delay in diagnosis and treatment will result in the involvement of the underlying periodontium, causing periodontal pockets, abscess formation, and bone loss, thereby further complicating the outcome. Appropriate diagnosis, education, and counseling of the patient by the dentist and coronal restoration following root canal treatment are mandatory to prevent the loss of teeth in patients. The prognosis of multirooted teeth is more favorable. Affected single-rooted teeth may, however, require immediate extraction. MEDLINE database and Scopus search (www.scopus.com) were performed using the key words “vertical root fracture” or “longitudinal root fracture.” Text book chapters were manually checked.
Keywords: VRF; cracked tooth; probing depth; bruxism; RCT; periodontal abscess